1999
DOI: 10.1093/jnci/91.2.163
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Eradication of Human BCR/ABL-Positive Leukemia Cells With an ABL Kinase Inhibitor

Abstract: These data indicate that the continuous block of the oncogenic tyrosine kinase of Bcr/Abl protein is needed to produce important biologic effects in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
188
0
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(200 citation statements)
references
References 11 publications
8
188
0
4
Order By: Relevance
“…Gleevec treatment produced a complete inhibition of tumor growth, indicating that a continuous block of Gleevec targets activity is needed to produce complete tumor regression. Similar results were observed when Gleevec was administered every 8 h in mice bearing Leydig cell tumors (Basciani et al, 2005) and in nude mice bearing Bcr/Abl-positive human leukemia cell lines (le Coutre et al, 1999). Discontinuation of Gleevec treatment resulted in rapid tumor re-growth, confirming the need for a sustained blockage of Gleevec targets to inhibit tumorigenesis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Gleevec treatment produced a complete inhibition of tumor growth, indicating that a continuous block of Gleevec targets activity is needed to produce complete tumor regression. Similar results were observed when Gleevec was administered every 8 h in mice bearing Leydig cell tumors (Basciani et al, 2005) and in nude mice bearing Bcr/Abl-positive human leukemia cell lines (le Coutre et al, 1999). Discontinuation of Gleevec treatment resulted in rapid tumor re-growth, confirming the need for a sustained blockage of Gleevec targets to inhibit tumorigenesis.…”
Section: Discussionsupporting
confidence: 71%
“…The length, width and depth of palpable tumors were measured with Vernier calipers. TW was determined using the equation TW (mg) ¼ (S) 2 Â L/2 where S and L (le Coutre et al, 1999) were measured in millimeters. S and L are the shortest and longest diameters of the tumor, respectively.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…It is interesting to note that bcr/abl constitute targets to the development of selective tyrosine kinase inhibitors. The avaibility of such inhibitors able to block bcr/abl tyrosine kinase constitutes a promising approach to the treatment of CML (Druker and Lydon, 2000; Lecoutre et al, 1999). Whether such compounds could reverse the constitutive activation of gc/Jak3 in leukemic progenitors should be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In many cancers, specific drugs are indicated for specific subtypes of cancer. Herceptin is only effective to the subpopulation of individuals with breast cancer who express ERBB2 (McNeil, 1998), and Gleevec is for individuals with chronic myeloid leukemia resulting from the BCR-ABL1 gene fusion (le Coutre et al, 1999). Similarly, two recent studies identified mutations in EGFR in lung adenocarcinomas, which predict response to the tyrosine kinase inhibitor gefitinib (Lynch et al, 2004;Paez et al, Figure 2 Comparative functional genomics.…”
Section: Comparative Functional Genomicsmentioning
confidence: 99%